EFISIENSI LUAS PANEN PADI DI PROVINSI SULAWESI SELATAN TAHUN 2018 - Ugiana Ramdhani (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
The food crop subsectors is one of the centers of attention in national development. Various efforts have been made to increase rice production, both through extensification of paddy fields and intensification of planting. South Sulawesi is one of the largest rice production centers in Indonesia in 2018 and deserves special attention in this regard. To be able to find out the right programs and efforts to increase rice production, information is needed regarding the potential and land use in the province of South Sulawesi. The study was conducted with mixed methods (qualitative and quantitative using data from the rice harvest area of South Sulawesi Province in 2018) which was simply analyzed using descriptive statistics to describe the results of data processing from the Central Bureau of Statistics, followed by in-depth interviews with six people to capture phenomenon that occurs in South Sulawesi. The efficiency of harvested area in South Sulawesi is currently 176.50 that caused by there is still land that is only harvested once a year or three times in two years so efforts need to be made to increase the efficiency of harvesting area through intensification of cropping.